The comprehension of clitic gender in child heritage and second language Spanish: evidence from a dual language program - Austin, Jennifer; Thane, Patrick D.; Rodríguez, Stephanie A.; Goldin, Michele (Frontiers in Language Sciences, 2024)
Differences in timing (age of acquisition) and in learning experience (through naturalistic exposure versus classroom-based instruction) set heritage speakers (HS) and second language (L2) learners (L2L) apart. HS acquire a language at home from birth in a social context where another language has more dominant status. They often do not receive academic instruction in this home language, and therefore many HS do not develop literacy skills in their heritage language. In contrast, most L2 learners begin to acquire a second language later in life, often through formal instruction, having already obtained literacy skills in their first language. By comparing the grammaticality judgements of these two groups, we can gain insights into how the experience of heritage versus L2 learners influences the development of bilingual grammars.Research on children enrolled in dual-language programs can also shed light on how the heritage language development is enhanced when HS have greater opportunities for sustained literacy and academic instruction throughout childhood and adolescence.In the United States, the rapid growth of dual language immersion programs in public schools provides HS with greater access to literacy and academic instruction in their heritage languages, and creates new opportunities for research on school-aged bilingual children.Dual-language immersion programs teach academic content such as math, science, reading and writing in English and a partner language, most frequently Spanish, given its prevalence in many U.S. communities. There are several recent studies that examine language acquisition in children